THE INFLUENCE OF THE PRINCIPAL SUPERVISION AND TEACHER'S PROFESSIONAL COMPETENCE IN LEARNING DESIGN ON THE QUALITY OF EDUCATION - SOLIHAH, Anis (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2023)
This study aims to analyze the effect of (1) principal supervision, (2) teacher professional competence and (3) learning design on education quality. The research method used is a causal survey with a correlational design and path analysis (Path Analysis). Correlational design is used to determine the relationship and the magnitude of the influence between two or more variables. The variables used in this study are the supervision of the principal (X_1), teacher professional competence (X_2), learning design (X_3), and quality of education (Y1). The population in this study were 182 public elementary school teachers in Cluster 2, Tangerang District. Validity test is calculated using the Product Moment formula and reliability is calculated using the Alpha Cronbach formula. The data were analyzed using descriptive statistics, to test the hypothesis, the correlation test, regression test and determination test were used which were calculated using SPSS version 25 software. The results showed that the supervision of school principals, teacher professional competence and learning design had an influence on the quality of education partially or simultaneously. Based on the results of the research, it can be implied that the supervision of the principal, teacher professional competence and learning design for teachers at SD Negeri Gugus 2 Tangerang District is good and this needs to be improved through teacher competency test activities, making good learning designs and optimizing the role of school principals so that quality the quality of education is getting better.